Enhancing hydrophobicity of electrospun poly(vinyl alcohol) fibers by chemical reaction of hydroxyl groups - Navarun Chaim-Ngoen (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2007